Analisis Daya Rusak Aliran Permukaan Berbasis Hidrologi Forensik pada Banjir Bandang Sub DAS Way Kuripan, Lampung: Forensic Hydrological Analysis Of Surface Flow Destructiveness In Flash Flood Events: Case Study Of Way Kuripan Sub-Dash - Muhammad Hakiem Sedo Putra; M. Ridho Ulya (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2026)
Flash floods are one of the most destructive forms of water destructiveness, but have not been studied quantitatively at the sub-watershed level in Indonesia. This study aims to assess the mechanism of surface flow destructive power through a forensic hydrology approach in a flash flood event in Way Kuripan Subwatershed, Lampung, which occurred in January 2024. This research combines hydrological simulation using SCS-CN and HEC-HMS methods with spatial analysis and field measurements in an integrated manner. Data on rainfall, topography, land use, and documentation of infrastructure damage were used to calculate damage parameters such as stream power and shear stress spatially. The simulation results showed that the peak discharge reached 132.5 m³/s due to extreme rainfall of 128 mm/day, while the highest stream power values exceeded 400 W/m² in steep, narrow, and low hydraulic radius channel segments. Spatial overlays between the damaging power map and field damage points showed a high match, confirming the validity of the forensic approach used in this study. The findings show that a combination of quantitative and visual spatial approaches can provide a comprehensive picture of the causation of water disasters. The forensic hydrology approach can be a powerful tool in reconstructing catastrophic events, understanding the destructive characteristics of surface flows, and supporting flood risk mitigation efforts.